EFFECT OF FOLIAR SPRAYING WITH SEAWEED EXTRACT (ACADIAN) AND CHELATED IRON ON THE GROWTH AND YIELD OF CORMS OF GLADIOLUS HYBRIDA (CARTAGO) (British Journal of Global Ecology and Sustainable Development, 2022)
The study was conducted in the wooden canopy of the Department of Horticulture and Landscape Engineering / College of Agriculture / University of Kirkuk, for the period from October 1, 2020 to May / 2021, to find out the effect of foliar spraying with a concentration of (0.1) g.l-1 for each of Seaweed extract and chelated iron in the growth and production of corms of Gladiolus hybrida of the cultivar (Cartago), the factorial experiment was designed according to the randomized complete block design (R.C.B.D.), with three replications, and the results were summarized as follows : 1- Foliar spraying with organic fertilizer at a concentration of 1 g.l-1 gave a significant increase in the length of the longest leaf (91.19) cm, and the total number of leaves was (10.22) leaves. plant-1, the largest number of corms and cormels and their fresh weight, and the largest diameter of corms (1.23 corms. plant-1, 3.83 cormel. plant-1, 59.64 g, 7.86 g, 6.45 cm), respectively.